Screening of Promising Leucaen a Provenances for the Doon Valley - Purl, D. N.; Gupta, R. K.; Dhyani, S. K. (Indian Forester, 1989)
The four main types of Leucaena leucocephafa viz. Hawaiin, Salvador, Peruvian and Cunningham were screened in an arboretal study reveal that F-205 (K.8), F-206 (Peruvian) and F-132 (Salvador) are suitable for afforestation in Doon Valley.